The Italian validation of OSCI: The Organizational and Safety Climate Inventory - Platania, S.; Paolillo, A.; Silva, S. A. (Safety, 2021)
Although safety climate has been the object of multiple studies in the last thirty years, the relationship between safety climate and organizational climate has been scarcely investigated. The Organizational and Safety Climate Inventory (OSCI) was the first and only validated instrument to allow the assessment of organizational and safety climates simultaneously and by using the same theoretical framework. The present work investigated the psychometric properties of OSCI in an Italian sample at the group level; study 1 (N = 745) examined the factor structure of the scale by using confirmatory factor analyses. Study 2 (N = 471) advanced the original Portuguese validation by testing its measurement equivalence across gender and company sector through multiple-group confirmatory factor analyses. Results confirmed one higher-order factor structure with four first-order factors for both Organizational Climate and Safety Climate, with Organizational Climate predicting Safety Climate. Moreover, the scale was found to be invariant between men and women and between different types of company. Reliability, discriminant, and criterion validities of the scale showed very good values. Overall, the findings strengthened the original claim of the OSCI to be a valid and innovative instrument, which allows the identification of specific dimensions of safety climate, starting from a more general model of organizational climate.